Pengaruh Konsumsi Daun Torbangun terhadap Produksi ASI - Marlina, Marlina; Trianingsih, Indah; Sari, Adinda Juwita (Jurnal Kesehatan, 2022)
Babies who are not breastfed will be susceptible to infectious diseases. In 2016 the exclusive breastfeeding rate in South Lampung Regency was 49.76% while in 2018 it decreased to 47.08%. The purpose of this study was to determine the effect of torbangun leaf decoction on breast milk production in postpartum mothers. The research design used is a true experimental design, researchers can control all external variables that affect the course of the experiment. Researchers conducted measurements before and after the treatment/intervention was given to the treatment group/experimental group. By giving Torbangun leaf steeping water to determine its effect on breast milk production in postpartum mothers, there is an effect on breast milk production for breastfeeding mothers after consuming Torbangun leaf drink. The results of the study obtained data that the dependent t-test obtained a t-count value of 17.169 with a p-value of 0.000. It can be seen that the p-value indicates that there is a significant difference in milk production before and after the administration of the torbangun leaf drink. The average milk production of breastfeeding mothers as seen from the baby's weight in the control group was 108.3 grams. The average milk production of breastfeeding mothers as seen from the baby's weight in the experimental group was 356.6 grams. There is an effect of breastfeeding mothers' milk production after consuming torbangun leaf drink.